EMOTIVE ADJECTIVAL UNITS IN MODERN ENGLISH: SEMANTIC APPROACH - Natalia Melnychuk; Anna Symaka (Scientific Journal of Polonia University, 2023)
The article is devoted to the study of the functioning of the English adjectival emotive units denoting positive semantics as direct linguistic means of representing human emotional states that combine semantic and pragmatic components of meaning. The aim of this paper is to determine the semantic features of the adjectival emotive units with positive meaning in modern English. The defined approach to the aim of this investigation led to the use of those research methods that correspond best to its goals: in particular, definitional, componential, quantitative analyses, thanks to which the main characteristics of the English adjectival units denoting positive semantics were clarified and the emotive component in the structure of their meaning was revealed. The basis for the analysis of the emotive adjectives with positive semantics in the English lingual worldview is the principle of sustainability which brings to the fore the link of the language with reality, its correlation with extra-linguistic actuality.